Intravenous cyclophosphamide pulse therapy is effective for refractory Graves' ophthalmopathy - Tanikawa, Takahisa; Okada, Yosuke; Tanaka, Yoshiya (Journal of UOEH, 2006)
Graves' ophthalmopathy is the most frequent extrathyroidal manifestation of Graves' disease. Although glucocorticoids and orbital radiotherapy have been used and are effective for the disease, we often experience cases refractory to either therapy. We report here a case that did not respond satisfactorily to either therapy and was later successfully treated by intravenous cyclophosphamide (IV-CY) pulse therapy. A 31 year old woman presented with typical Graves' disease and ophthalmopathy. After establishing a euthyroid state, she received intravenous glucocorticoid pulse therapy and orbital radiotherapy. Although this induced the resolution of the ophthalmopathy, it was temporary and thyroid-stimulating antibody (TSAb) increased to high titers, associated with relapse of ophthalmopathy 2 months after the treatment. Four courses of IV-CY pulse therapy were administered, which resulted in complete improvement of the symptoms and normalization of the TSAb titers. We suggest that IV-CY pulse therapy might be useful for Graves' ophthalmopathy, especially for patients refractory to glucocorticoid pulse therapy.